2015
DOI: 10.2399/jmu.2015003006
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric analysis of the maxillary sinus in pediatric patients with nasal septal deviation

Abstract: Özet: Nazal septum deviasyonu olan pediatrik hastalarda maksiller sinüsün volümetrik analizi Amaç: Nazal hava ak›m›n› azaltan ve oksijenasyonu bozan septal deviasyon gibi sebepler, maksiller sinüs hacmini etkileyebilir. Çal›flma-m›zda, retrospektif olarak nazal septal deviasyonlar›n maksiller sinüs hacmini nas›l etkiledi¤ini araflt›rmay› amaçlad›k. Yöntem: Kulak burun bo¤az poliklini¤inde kronik bafla¤r›s› etiyolojisini ayd›nlatmak üzere paranazal sinüs bilgisayarl› tomografisi çekilen ve intrakraniyal bir seb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
1
0
1
Order By: Relevance
“…The development of maxillary sinuses may vary by age and person and they may show different development patterns. 7,12,13,14 In our study, ipsilateral and contralateral maxillary sinus volumes of 9- to 14-year age group were significantly lower than those of 15- to 17-year age group.…”
Section: Discussionsupporting
confidence: 41%
“…The development of maxillary sinuses may vary by age and person and they may show different development patterns. 7,12,13,14 In our study, ipsilateral and contralateral maxillary sinus volumes of 9- to 14-year age group were significantly lower than those of 15- to 17-year age group.…”
Section: Discussionsupporting
confidence: 41%
“…NSD is also associated with an increased prevalence of sinusitis (Kucybała et al, 2017). Very few studies have assessed MS growth in children and none have demonstrated a statistically significant difference regardless of the severity of deviation (Lee & Jin, 2014; Şentürk et al, 2015). In contrast, adult studies have reported a difference in MS volume in the deviated side in individuals with severe septal deviation (>15°) (Kalabalik & Ertas, 2018; Kapusuz Gencer et al, 2013).…”
Section: Pathological Processes That Affect Sinus Developmentmentioning
confidence: 99%
“…Paranazal sinüsün müköz membranının enflamasyonu sinüzit olarak adlandırılır. [1][2][3][4] Paranazal sinüsler, çocukluk döneminde erişkinlere göre hacim bakımından küçük olduğundan paranazal sinüs hastalıkları sıklıkla görülmektedir. Maksiller sinüsler en büyük bilateral paranazal sinüslerdir ve burun boşluğunun orta bölümüne tek veya çoklu ostium ile açılır.…”
Section: Introductionunclassified